PREVALENCE AND FACTORS ASSOCIATED WITH THE TRIGGERING OF INJURIES IN SENIOR WOMEN'S TEAMS IN MAPUTO CITY (REMUNOM, 2025)
This study analyzed the training context, injury prevalence, and associated factors among senior women's volleyball teams in Maputo, Mozambique. The methodology adopted a quantitative, descriptive approach, using an online questionnaire developed ex professo for data collection. This questionnaire was administered to 20 volleyball players who participated in various competitions in Maputo during the 2023 season. Statistical Package for Social Sciences (SPSS) v21 software was used for data analysis and processing. Given the sample characteristics, a nonparametric approach was adopted, using descriptive statistics, calculating relative and absolute frequencies, and association analysis of categorical variables using Fisher's exact test, with effect size measured using Cramer's V. The significance level was set at p≤0.05. The results highlight a significant prevalence of sprains, especially in the ankles, followed by muscle injuries, with athletes playing in more physically demanding positions, such as center players, being more affected. The main causes identified were direct and indirect trauma, as well as repetitive overload. The conclusion is that it is necessary to incorporate proprioception and balance training to prevent sprains, especially in the ankle, identified as the most common injury among athletes, and to promote regular educational sessions for athletes and coaches on the importance of injury prevention, safe training techniques, and self-care practices